Operation car wash: Brazil's institutionalized crime, and the inside story of the biggest corruption scandal in history - Pontes, Jorge (Bloomsbury Academic, 2022)
"Operation Car Wash is the inside story of two Brazilian Federal Police officers who found themselves at the centre of the biggest corruption scandal in history; uncovering an web of political and corporate racketeering which would lead them all the way to the arrest and imprisonment of the nation's President. Through engrossing first-hand testimony, Pontes and Anselmo recount the uphill battle faced by the Federal Police in apprehending Brazil's white-collar criminals, in a country where the war on drugs has become a convenient distraction for the politicians and businessmen extracting billions of dollars from the public purse. A historical record that reads like a political police thriller, Operation Car Wash is also a warning to the world: demonstrating how easily institutionalized crime can take root in a nation, and how difficult it can be to eradicate"--